An iterative receiver for quantized MIMO systems - Mezghani, A.; Rouatbi, M.; Nossek, J. A. (2012 16th IEEE Mediterranean Electrotechnical Conference, 2012)
We study the joint optimization of the quantizer and the iterative Decision Feedback Equalizer (IDE) for the flat multi-input multi-output (MIMO) channel with quantized outputs. Our design is based on a minimum mean square error (MMSE) approach, taking into account the effects of quantization. Our derivation does not make use of the assumption of uncorrelated white quantization errors and considers the correlations of the quantization error with the other signals of the system. Through simulation, we compare the provided IDE to the conventional spatial DFE operating on quantized data in terms of uncoded BER.